A modified lead-user approach for new product development: an illustration from the US of a marketing research tool for the forest industry. (August 2015) - Hansen, E.; Knowles, C.; Larson, K.
Abstract : Innovation is critical for firm success, including forest sector firms. However, historically forest sector firms have focused on process over product innovations. Additionally, research shows that forest sector firms often fail to have a structured new product development (NPD) process. The purpose of this work is to illustrate use of the lead-user method to identify user-lead ideas for innovation within the wood-window value chain, thereby demonstrating the potential of a modified lead-user approach as a NPD tool for the forest industry. Personal interviews with 22 individuals were conducted with sales agents, installation experts, homebuilders, and architects. Findings outline opportunities for the introduction of new products/services, thereby demonstrating the value of relying on lead-users for identifying potential products. This study also highlights the challenges associated with the lead-user methodology, including the varying definitions of a lead-user and the subjective nature of categorising someone as a lead-user.